2006
DOI: 10.1163/156854106778493394
|View full text |Cite
|
Sign up to set email alerts
|

Source of trait deterioration in entomopathogenic nematodes Heterorhabditis bacteriophora and Steinernema carpocapsae during in vivo culture

Abstract: The stability of traits important for biological control was studied in the entomopathogenic nematode-bacteria complexes Heterorhabditis bacteriophora and Steinernema carpocapsae. Five experimental lines of each species were subcultured for 20 serial passages in Galleria mellonella larvae to assess trait stability. Subculturing impaired performance of both H. bacteriophora and S. carpocapsae. Virulence, heat tolerance and fecundity deteriorated in all H. bacteriophora experimental lines, and four out of five e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Trait deterioration can be genetically based (e.g., inbreeding, drift, inadvertent selection), or stem from non-genetic factors (e.g., disease or nutrition) (Chaston et al, 2011;Hopper, Roush, & Powell, 1993;Tanada & Kaya, 1993). Deterioration in EPNs has been observed under laboratory conditions for various traits such as virulence, environmental tolerance, reproductive capacity, and host-finding (Bai, Shapiro-Ilan, Gaugler, & Hopper, 2005;Bilgrami, Gaugler, Shapiro-Ilan, & Adams, 2006;Shapiro, Glazer, & Segal, 1996;Wang & Grewal, 2002). Both the nematodes and their bacterial symbionts may experience trait loss (Bilgrami et al, 2006;Wang et al, 2007).…”
Section: Improved Methods Of Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Trait deterioration can be genetically based (e.g., inbreeding, drift, inadvertent selection), or stem from non-genetic factors (e.g., disease or nutrition) (Chaston et al, 2011;Hopper, Roush, & Powell, 1993;Tanada & Kaya, 1993). Deterioration in EPNs has been observed under laboratory conditions for various traits such as virulence, environmental tolerance, reproductive capacity, and host-finding (Bai, Shapiro-Ilan, Gaugler, & Hopper, 2005;Bilgrami, Gaugler, Shapiro-Ilan, & Adams, 2006;Shapiro, Glazer, & Segal, 1996;Wang & Grewal, 2002). Both the nematodes and their bacterial symbionts may experience trait loss (Bilgrami et al, 2006;Wang et al, 2007).…”
Section: Improved Methods Of Applicationmentioning
confidence: 99%
“…Deterioration in EPNs has been observed under laboratory conditions for various traits such as virulence, environmental tolerance, reproductive capacity, and host-finding (Bai, Shapiro-Ilan, Gaugler, & Hopper, 2005;Bilgrami, Gaugler, Shapiro-Ilan, & Adams, 2006;Shapiro, Glazer, & Segal, 1996;Wang & Grewal, 2002). Both the nematodes and their bacterial symbionts may experience trait loss (Bilgrami et al, 2006;Wang et al, 2007). The cause of trait deterioration in EPNs (H. bacteriophora) was reported to be genetically based with inbreeding depression being the prominent issue (Adhikari et al, 2009;Bai et al, 2005;Chaston et al, 2011).…”
Section: Improved Methods Of Applicationmentioning
confidence: 99%
“…Indeed, artificial rearing conditions themselves could have an important influence on the development and reproduction of EPNs, alter the dynamics involved, and select for an array of different traits from those that are important in nature. This kind of inadvertent selection has been documented for laboratory cultures of EPNs (Bilgrami, Gaugler, Shapiro-Ilan, & Adams, 2006; and could influence the establishment and persistence abilities of mass-reared nematodes when applied in the field.…”
Section: Intraspecific Competition and Cooperation Among Entomopathogmentioning
confidence: 99%
“…However Bai et al (2005) found that inbred lines of H. bacteriophora can prevent beneficial trait decline by causing greater mortality to host insects than foundation populations. Bilgrami et al (2006) found that the loss of virulence against G. mellonella larvae was the result of bacterial deterioration during subculturing.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory culture of EPN may have detrimental effects on laboratory populations due to, for example, selection under artificial conditions and inbreeding depression (Stuart & Gaugler, 1996;Bilgrami et al, 2006). Costa et al (2007) state that factors such as the virulence of the symbiotic bacteria, species of host used, concomitant infection with another organism, and the number of penetrated IJ, can affect the multiplication potential of EPN.…”
mentioning
confidence: 99%